Mitigating techniques for the operational challenges of a standalone hybrid system integrating renewable energy sources - Arul P.G.; Ramachandaramurthy V.K. (Elsevier Ltd, 2023)
Electric batteries; Electric frequency control; Energy resources; Energy storage; Hybrid systems; Maximum power point trackers; Natural resources; Power control; Reactive power; Renewable energy resources; Solar power generation; System stability; Voltage control; Wind turbines; Active and reactive power controls; Bus regulation; Droop control; Hybrid renewable energy systems; Maximum Power Point Tracking; Renewable energy source; Stand-alone hybrid system; Voltage and frequency control; Quality control; alternative energy; control system; electricity supply; energy resource; operations technology; photovoltaic system; power generation; renewable resource; solar power; technology adoption; wind power; wind turbine